Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $a,b,c$ positive real numbers such that $a+b+c=3$, using only AM-GM inequalities show that $$ a+b+c \geq ab+bc+ca $$ I was able to prove that $$ \begin{align} a^2+b^2+c^2 &=\frac{a^2+b^2}{2}+\frac{b^2+c^2}{2}+\frac{a^2+c^2}{2} \geq \\ &\geq \frac{2\sqrt{a^2b^2}}{2}+\frac{2\sqrt{b^2c^2}}{2}+\frac{2\sqrt{a^2c^2}}{2}= \\ &= ab+bc+ca \end{align} $$

but now I am stuck. I don't know how to use the fact that $a+b+c=3$ to prove the inequality. Anybody can give me a hint?

share|cite|improve this question
up vote 2 down vote accepted

Update: Upps, that is the same as that of @Vincent, sorry didn't see that first. However, it's a bit more explicte

A nicer way to use your results and proceed frm there is the following. You've got that $$ a^2+b^2+c^2 \ge ab+bc+ca $$ Now use the fact that $(a+b+c)=S=3$ and multiply each side of your original inequality by S this is $$ (a+b+c)S \ge S(ab+bc+ca)$$ or, (where we use now that $S=3$) $$ (a+b+c)(a+b+c) \ge 3(ab+bc+ca)$$ Then $$ a^2+b^2+c^2 + 2(ab+bc+ca) \ge 3(ab+bc+ca)$$ and $$ a^2+b^2+c^2 \ge ab+bc+ca$$ which is exactly that, what you've already proven on your own.

share|cite|improve this answer
It was that easy! I didn't see it, thank you. – Emmet Feb 27 '13 at 10:30
Ok, but now that I think about it... How to proceed from that? Any idea? – Emmet Feb 27 '13 at 10:39
hmm, after that you've done the work, and you can proceed to the cafeteria... ;-) – Gottfried Helms Feb 27 '13 at 15:22

$$9=(a+b+c)^2=a^2+b^2+c^2+2(ab+bc+ca)\geq 3(ab+bc+ca)$$

share|cite|improve this answer
Thank you very much. – Emmet Feb 27 '13 at 10:30

Hint: Multiply the original inequality by $a+b+c$ on the LHS and $3$ on the RHS, expand and eliminate common terms and you will arrive at something you have proved.

share|cite|improve this answer
Thank you very much. – Emmet Feb 27 '13 at 10:30

$9 = (a + b + c)^2 = a^2 + b^2 + c^2 + 2(ab+bc+ac) \geq 3(ab+bc + ac)$

share|cite|improve this answer
Thank you very much. – Emmet Feb 27 '13 at 10:32

Reformulate first $a+b+c=S$ and $a=M+d \qquad b=M-d $ then

$$S \ge M^2-d^2 + (S-2M)2M$$ reorganize $$ 3M^2-2SM+S +d^2 \ge 0 $$

Now make use of the given definition that $S=3$. We get $$3(M^2-2M+1) +d^2 \ge 0 $$ $$3(M-1)^2 +d^2 \ge 0 $$ which is always true.

Well, this focuses "when and how" it makes sense to introduce the condition that $S=3$. Unfortunately the step with the AM-GM-inequality is lost. But maybe you can combine your steps with this derivations?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.